Morphological and molecular characterization of Colletotrichum spp. from citrus orchards affected by postbloom fruit drop in Brazil - KuramaeIzioka, E. E.; Lopes, C. R.; Souza, N. L.; Machado, M. A. (Kluwer Academic Publ, 1997)
Brazilian isolates of Colletotrichum spp. from citrus orchards affected by postbloom fruit drop were examined for colony colour, mycelial growth, benomyl-resistance, pathogenicity, and genetic variability by random amplified polymorphic DNA (RAPD) analysis. All isolates were obtained from flowers and persistent calyxes from different citrus hosts from São Paulo, Brazil. DNA polymorphisms detected after amplification with random 10-mer primers were used to classify the isolates into two groups. Group I isolates grew rapidly on potato-dextrose agar (PDA) and were sensitive to benomyl, and group II isolates grew slowly on PDA and were benomyl-resistant. Colletotrichum acutatum was analyzed by RAPD and had high genetic similarity with group II isolates of Colletotrichum from citrus. Probably, the group I is C, gloeosporioides and group II is C. acutatum.
Keywords: Colletotrichum acutatum; citrus postbloom fruit drop disease; RAPD